Main directions of research work of the department of Russian language - Rovdo, Ivan S. (Journal of the Belarusian State University. Philology, 2024)
The scientific activity of the department of Russian language of the faculty of philology of the Belarusian State University of the late 20th and early 21st century is considered. Basic research in the 21st century is listed, much of which is related to the comparative study of modern Russian, Belarusian and other languages. Attention is drawn, in particular, to the research of Russian, Belarusian, and foreign onomastics, the study of the language of fiction and media texts, the identification of some facts when comparing Russian and Belarusian lexicon, the training of doctors of science and PhD. It is confirmed that an important role in realising the scientific potential of the department’s employees belongs to the former heads of the department, professors M. G. Bulakhov and P. P. Shuba.
Keywords: department of Russian language; scientific work; onomastics; media language; shuttle translation; M. G. Bulakhov; P. P. Shuba